Taller de Fonética y Fonología basado en tareas para mejorar las capacidades comunicativas orales del inglés en los estudiantes del quinto año de la Especialidad de Idiomas de la Universidad Nacional de Trujillo, en el 2010 - Del Rosario Alfaro, José Leonardo (2011)
This study was carried out with the purpose of determining to which extent the Task - Based Workshop in Phonetics and Phonology improves the oral communication skills of English students of the fifth year of the Specialty of Languages of the National University of Trujillo, in the year 2010. The research work had as a sample population thirty four students of the Specialty of Languages of the National University of Trujillo, who have similar academic and social characteristics. The research type is technological with a pre-experimental design with a single pretest and postest group. The Task – Based Phonetics and Phonology Workshop was developed in six teaching-learning sessions. After applying it, it was found that the oral English communication skills improved significantly. The same situations occurred with its dimensions: Listening comprehension in 3.70, oral interaction in 6.38 and 6.91 for oral production as an improvement in its condition of experimental group, which went from the initial condition of sufficient to satisfactory.